Effect of detomidine injection on clinical indicators, biochemical and hematological parameters in camels (Journal of Hama University, 2023)
Detomidine was injected intravenously at a dose of (25 μg/kg) into six camels male  whose ages ranged between (3-4.5) years, and their weight was approximately (400-300) kg, in order to study the effect of this antitussive on some clinical indicators (heart rate). And the rate of breathing movements and body temperature) and some blood parameters (white blood cells, red blood cells, hemoglobin, hematocrit and platelets) as well as some biochemical parameters (glucose, creatinine, sodium ion, potassium, chlorine,  activity ALT and AST). Where blood samples were taken before the injection and 15-30-60-120 minutes and 24 hours after the injection.The results of detomidine injections in camels showed a decrease in heart rate and breathing movements after 30-60 minutes (P≤0.05), and no significant changes in body temperature (P≤0.05) were observed.As for the hematological parameters, a significant decrease was observed in the number of white blood cells per minute (15) after the injection (P≤0.05), while the platelets did not have any significant change (P≤0.05). As for the number of red blood cells, hemoglobin, a significant decrease was noted After (24) hours (P≤0.05).As for the biochemical parameters, a significant increase in blood glucose was observed from (15) to (120) minutes after the injection (P≤0.05), and a significant decrease (P≤0.05) in sodium and chlorine (24) hours after the injection, and no change was observed. Significant increase in potassium and creatinine (P≤0.05), while for the  activity enzyme ALT, AST a significant increase was observed (24) hours after injection (P≤0.05).
Keywords: Camel; Detomidine; Haematological Parameters; , Bbiochemical